Answer:
[tex]y = -2x +3\\\rule{150}{0.5}\\\text{Slope: -2}\\\text{Y-Intercept: 3}[/tex]
Step-by-step explanation:
We would have to convert the standard equation into slope-intercept form.
======================================
[tex]8x + 4y = 12\\\rule{150}{0.5}\\8x - 8x + 4y = 12-8x\\\\4y = 12-8x\\\\4y = -8x + 12 \leftarrow \text{I switched the order on the right side.}\\\\\frac{4y=-8x+12}{4}\\\\\boxed{y = -2x + 3}[/tex]
======================================
General slope-intercept form is:
[tex]y=mx + b\\\rule{150}{0.5}\\\text{m - Slope}\\\text{b - Y-Intercept}[/tex]
In the equation [tex]y = -2x + 3[/tex], '-2' would be the slope since it is in 'm's place, and '3' would be the y-intercept since it's in 'b's place.
Therefore:
[tex]\text{In } y=-2x+3\text{...}\\\rule{150}{0.5}\\\text{Slope: -2}\\\text{Y-Intercept: 3}[/tex]
======================================
Hope this helps!